VET teacher education – a co-constructive design process - Hantsch, Robert [Verfasser]; Hantke, Harald [Verfasser] (My University, 2024)
“VET (vocational education and training) teacher education is intended to foster professional competence and continuous learning for teachers throughout their careers. Even though teacher education in Germany is anchored in subject-specific sciences, subject-specific didactics (vocational), educational sciences, and practical experience, fragmentation and discontinuity persist. The article addresses these challenges in a systematic manner, integrating structures, content, and stages to achieve coherence. Using a case study from the federal state of Mecklenburg-Vorpommern, we identify, understand, and propose solutions for improving coherence in VET teacher education. Through a design-based research approach, we propose prototypes for cross-stage and cross-institutional collaboration, emphasizing the need for such partnerships to address issues of coherence.” (authors’ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; S 1.4 Hochschulbildung; 370; Berufsschullehrer; Lehrerausbildung; Fallstudie; Mecklenburg-Vorpommern